(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: There is still divergence in the literature about salivary changes during the gestational period. Objectives: To evaluate the flow, pH and buffer capacity of the saliva of women in the gestational and postpartum period and compare it with non-pregnant women. Methods: The prospective case-control study with convenience sample between pregnant (P) and non-pregnant women (NP). The stimulated collection was performed in the morning during gestation and powder-delivery. Data were analyzed by the Shapiro-Wilk, t-Student, Mann-Whitney and Friedman tests (p <0.05). Results: There were 17 pregnant, with a mean age of 26.1 ± 4.4 years old; and 28 non-pregnant women, with an average of 24.4 ± 4.4 years old. There was a difference in salivary flow (p=0.023) and in the buffer capacity (p=0.033) between P and NP in the postpartum period, as well as in saliva pH at 20th (p=0.007) and 30th weeks (p=0.010) of gestation. In the group of pregnant women, saliva flow and pH did not change during gestation and postpartum (p> 0.05). However, the saliva buffer capacity increased postpartum (p <0.001). Conclusion: The salivary flow and buffer capacity of the pregnant women were lower in the postpartum period, and the saliva pH was lower in the gestational period (20th and 30th weeks) when compared to the group of non-pregnant women. Among the pregnant women, there was no change in the salivary flow and pH of the saliva, but there was an increase in the buffer capacity of the saliva at follow-up time.